2010
DOI: 10.1093/schbul/sbp166
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the env Gene of the Human Endogenous Retrovirus W Family in the Expression of BDNF and DRD3 and Development of Recent-Onset Schizophrenia

Abstract: Objective: Retrovirus has been suggested as one of agents involved in the development of schizophrenia. In the present study, we examined the role of the human endogenous retrovirus W family (HERV-W) env gene in the etiopathogenesis of recent-onset schizophrenia, using molecular and epidemiological approaches. Methods: Nested RT-PCR was used to detect the messenger RNA (mRNA) of the HERV-w env gene in plasmas. Quantitative real-time polymerase chain reaction (PCR) was employed to detect the viral reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 53 publications
4
93
0
2
Order By: Relevance
“…47 This finding suggests a role of HERV-W in schizophrenia-associated BDNF and DRD3 abnormalities. Some HERVs use neuroactive molecules as receptors.…”
Section: Pathological Liaisons Of Herv-wmentioning
confidence: 91%
See 1 more Smart Citation
“…47 This finding suggests a role of HERV-W in schizophrenia-associated BDNF and DRD3 abnormalities. Some HERVs use neuroactive molecules as receptors.…”
Section: Pathological Liaisons Of Herv-wmentioning
confidence: 91%
“…Huang et al 47 sought to detect genes with mRNA sequences homologous to the HERV-W env gene in the plasma of 118 patients with recent-onset schizophrenia and 106 normal control participants. The authors found the genes in 42 of 118 patients (35.6%) but in none of the control participants.…”
Section: Association Of Herv-w With Schizophreniamentioning
confidence: 99%
“…Cette augmentation a également été retrouvée au niveau des cellules mononucléées du sang (PBMC) isolées des patients entrant dans la schizophrénie avec une expression accrue de HERV-W gag, de 2 fois par rapport aux témoins [27]. Une corrélation inverse entre niveau d'expression du HERV-W et durée de la maladie semble aussi exister [27] et HERV-W env est surexprimée chez les sujets SCZ et TB [28], associée à une activité transcriptase inverse augmentée d'environ 36 % [29]. La présence dans le sang, d'antigènes codés par HERV-W gag et HERV-W env est observée chez environ la moitié des patients SCZ (des mêmes patients étant positifs pour les deux antigènes, la révélation de HERV-W env étant réalisée par deux anticorps monoclonaux différents) [30].…”
Section: Les Herv Dans La Schizophrénie Et Le Trouble Bipolaireunclassified
“…Gene-environment interactions may be involved in the development of vulnerability and prominent negative symptoms may be regarded as a characteristic of severe type of the disorder, possibly associated with neurodegeneration (Tsuang, 2000;Huang et al, 2011). Connections between the onset of schizophrenia and viral infections are reported, indicating that viral infections may play a role in the etiopathogenesis of schizophrenia (Arias et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of them have become mutated and truncated, a few have retained the capacity to encode viral proteins, still contain intact promoters or are able to form virus-like particles (Boller et al, 2008). Moreover, novel HERV loci can be generated by recombination/(retro) transposition during gestation, creating modifications in the embryonic DNA (Subramanian et al, 2011), and some HERVs are mobile genetic elements which may be regulated/activated by environmental factors, such as microbial agents, and can induce genetic rearrangements (Huang et al, 2011;Feschotte and Gilbert, 2012). An association between endogenous retrovirus activation and schizophrenia has been supported by several studies (Lillehoj et al, 2000;Yolken et al, 2000;Karlsson et al, 2001Karlsson et al, , 2004Perron et al, 2008;Leboyer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%